Guidelines for the inpatient treatment of severely malnourished children - Ashworth, A. (Ann) (World Health Organization, 2003)
Severely malnourished children need special care. This book provides simple, practical guidelines for treating these children successfully and takes into account the limited resources of many hospitals and health units in developing countries. It is intended for doctors, nurses, dietitians and other health workers with responsibility for the medical and dietary management of severely malnourished children, and for their trainers and supervisors. The guidelines are authoritative and hospitals using them report substantial reductions in mortality. For example, mortality rates of 30-50% have fall.